AN ANALYSIS OF SELECTED ED SHEERAN’S SONGS LYRIC IN PERFECT, SHAPE OF YOU, AND PHOTOGRAPH DISCOURSE ANALYSIS APPROACH - Kemal, Edwar; Damayanti, Muthia (Journal of Pragmatics and Discourse Research, 2021)
Song is a kind of literature art that expresses many aspects of life. It can provides usmore than pleasure of imagination. Ed Sheeran’s  is a musician and a music playing guitar at a young age and soon after started writing his own songs. Since signing with Atlantic, Sheeran has sold millions of records, had a song appear in the second installment of The Hobbit trilogy and won Grammys. The purpose of this research is to analyze the connotative meaning in selected Ed Sheeran’s songs lyric. The researcher uses content-analysis because the data that the researcher uses and takes is a song lyric. Result in this research is Ed Sheeran’s uses Frienliness and Happiness connotative in his lyrics to the listener in a encouraging way, something that makes the listener easy to understand knowing what is the connotation in the lyric.